2017
DOI: 10.1088/1748-3190/12/1/015002
|View full text |Cite
|
Sign up to set email alerts
|

An active electrolocation catheter system for imaging and analysis of coronary plaques

Abstract: Coronary artery disease-currently one of the most frequent causes of death-is characterized by atherosclerotic plaques grown in the wall of blood vessels and inhibiting blood flow. Preventive assessment focusses on critical sizes of structural plaque parameters like relative lipid core area and cap thickness to identify high-risk plaques called thin cap fibroatheromas. Although state-of-the-art catheter systems were successfully applied in invasive plaque diagnostics, the high costs induced by these devices in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…On a broader scope, the similar computational ''goals and strategies'' [15] underlying both types of color sensing and resembling aspects of color traits suggest color perception as a sensory concept beyond vision and passive sensing. Beyond biology, our findings might help improve recent biomimetic applications (i.e., technical versions of the active electric sense) used, e.g., for analysis of atherosclerotic plaques in blood vessels [40] or underwater object inspections [e.g., 41].…”
Section: Figure 4 Prey Recognition For Artificial Stimulus Objectsmentioning
confidence: 99%
“…On a broader scope, the similar computational ''goals and strategies'' [15] underlying both types of color sensing and resembling aspects of color traits suggest color perception as a sensory concept beyond vision and passive sensing. Beyond biology, our findings might help improve recent biomimetic applications (i.e., technical versions of the active electric sense) used, e.g., for analysis of atherosclerotic plaques in blood vessels [40] or underwater object inspections [e.g., 41].…”
Section: Figure 4 Prey Recognition For Artificial Stimulus Objectsmentioning
confidence: 99%
“…9 This idea combines the ability of active electroreception to evaluate surface texture with the possibility to detect capacitive elements as plates of atheroma due to the deposit of cholesterol. In this case, the authors tested two models: the first with one ring electrode which can obtain dynamic one-dimension electric images and the second with 16 (4x4) ring electrodes which can obtain dynamic and static electric images.…”
Section: Artificial Electric Sensorsmentioning
confidence: 99%
“…Research on artificial electroreception was boosted after this modality was implemented in underwater robots, 7 electrotomography and intravascular catheters for medical and other purposes. 8,9 This review focuses on the bioinspiring potential of research in natural electroreceptors, the present models that could be artificially implemented and the importance of waveform sensing receptive mosaics to medical and non-medical devices. Discussion is organized in three chapters dealing with electroreception in aquatic animals, natural sensors, bioinspired artificial sensors and the present models for waveforms sensing artificial sensors.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of electrosensory and electromotor systems have shed light on a wide range of issues in neuroscience, evolutionary biology, and ecology as well as providing inspiration for the development of artificial sensors and robotics systems. [3][4][5] Although the early stages of electrosensory processing have been extensively studied in a number of species, the lack of and water absorption rate. [11] Viventi et al (2011) demonstrated an actively multiplexed highly-dense electrode array for mapping in vivo brain activity using flexible silicon technology.…”
Section: Introductionmentioning
confidence: 99%